The role of diplomacy in settling borders in Prekmurje after the World War I. - Raščan, Stanislav (Anali PAZU HD, 2022)
In Slovenia there are many scientific and popular literature written on the settling of the northern boundary Carinthia and westhern boundaries Primorske, after World War I. About regulation of national borders in Prekmurje was not written much. This is probably due to the fact that the Yugoslavian and Slovenian delegation at the peace conference in Paris was more committed to Carinthia and Primorsko, while the Prekmurje and Styria belonged to Slovenia and then the Kingdom of Serbs, Croats and Slovenes, thanks to some excellent diplomatic negotiator and strong military interventions that have supported the diplomatic efforts. When connecting the Prekmurje to the Motherland contributed a positive or at least neutral stance of the then superpowers and the winners of the Great War the United States, Britain, France, Japan and Italy. The majority of winning powers also sent their diplomats to the border area between Slovenia and Hungary, so that they are also oversee the settling of the borders.
Keywords: diplomacy; Prekmurje; World War 1.; peace conference in Paris